The Position of Online Petitions in The Indonesian Legal Order - Shohib Muslim; Kalijunjung Hasibuan; Didik Suhariyanto; Nugrah Gables Manery; Lisbet Situmorang (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
This research is a qualitative research with a descriptive approach, namely describing the position of Online Petitions in the legal order in Indonesia and also describing its position in the legal order in European countries. The data used in this research is secondary data that researchers obtained from scientific articles, books, statutory regulations, magazines and credible websites that are commonly used and become references in each research. The data used was analyzed using descriptive and comparative legal analysis techniques, namely first describing the position of online petitions in Indonesian legal matters and then comparing them with various European countries. The result in this research show that that the regulation of online petitions in Indonesia is not very detailed and roams freely. This means that online petitions that have been filled in in large numbers exceeding the threshold in countries such as the UK and the United States which must be answered by the government, do not have to be answered in Indonesia. Online petitions are a form of product of freedom of expression from democracy. On the one hand, researchers believe that more specific arrangements for handling online petitions such as the United States and England also need to be implemented in Indonesia. However, on the other hand, this is not really necessary due to the responsive nature of the Indonesian government in answering the big questions on the minds of the public. Apart from that, these big questions are more often discussed through various talk shows, whether via digital television, print media, Instagram, YouTube and other platforms. For these various reasons, researchers believe that further regulation regarding online petitions is not really necessary in Indonesia. In fact, researchers are of the opinion that making a case go viral on social media without packaging it in the form of a petition is more effective than organizing the online petition itself.